Notes on the Leonard System Classification - Terwilliger, Paul (Graphs and combinatorics, 2021)
Around 2001 we classified the Leonard systems up to isomorphism. The proof was lengthy and involved considerable computation. In this paper we give a proof that is shorter and involves minimal computation. We also give a comprehensive description of the intersection numbers of a Leonard system.